CORPORATE SOCIAL RESPONSIBILITY AND FINANCIAL PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA - ARIYIBI, MAYOWA; Isiag, K, Olaiya; Olufemi, Adebayo (TRIPUTRA : Sosial, Ekonomi dan Hukum, 2024)
The role of deposit money banks in bridging the intermediation gap in the financial system plays a vital role in influencing the economy's capacity for saving and investment. The extent to which these banks prioritize corporate social responsibility, encompassing the interests of various internal and external stakeholders, determines their effectiveness in fulfilling their intermediary role. This research investigates the impact of corporate social responsibility on the financial performance of Nigerian deposit money banks. The study focuses on a selected group of deposit money banks in Nigeria, analyzing secondary panel data from 2017 to 2022. Panel regression analysis is conducted to explore the relationship between corporate social responsibility (measured through investment and binary approaches) and two financial performance indicators: non-performing loans and net interest income. The results obtained from the random effect model indicate that corporate social responsibility, particularly when measured using the investment method, has a statistically significant positive influence on non-performing loans. Conversely, the binary approach to corporate social responsibility has a statistically significant negative effect on net interest income. The study concludes that deposit money banks should continue practicing corporate social responsibility throughout their fiscal year as it enhances intermediation skills and reduces the occurrence of non-performing loans.